Analisis Pelatihan dan Pengembangan Sumber Daya Manusia Pada Perusahaan Jasa - Arman Maulana (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Employee training and development is one of the most important activities in an organization. Training opportunities help employees enrich their knowledge and improve performance. It is therefore important to provide training opportunities for employees and strengthen these practices, but this is not one of the priorities of some organizations. The main objective of this research paper is to evaluate employee training and development practices in organizations and to recommend adjustments for their increased use. Various information was collected from the results of documentation and observation studies using qualitative methods. Analysis of this information reveals that employees have a good attitude towards training as it improves their performance, but they are not satisfied with the company's current training practices. The role of training and development is currently decentralized and empowers managers to provide training to employees, but in reality no guidelines or policies exist to guide training and even training documentation is not properly maintained. Based on these results, training is recommended as a centrally coordinated activity that strengthens existing training mechanisms and provides development opportunities to employees to enrich their knowledge and experience.